2018
DOI: 10.1038/s41598-018-21793-0
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution 3D photopolymerization assisted by upconversion nanoparticles for rapid prototyping applications

Abstract: Three-dimensional (3D) rapid prototyping technology based on near-infrared light-induced polymerization of photocurable compositions containing upconversion nanomaterials has been explored. For this aim, the rationally-designed core/shell upconversion nanoparticles NaYF4:Yb3+,Tm3+/NaYF4, with the distinct ultraviolet-emitting lines and unprecedentedly high near-infrared to ultraviolet conversion efficiency of have been used. The upconverted ultraviolet photons were capable to efficiently activate photoinitiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
68
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(71 citation statements)
references
References 35 publications
2
68
0
1
Order By: Relevance
“…Recently, a high-resolution 3D photopolymerization was developed in which UCNPs, dispersed in a liquid mixture of photocurable composition, emitted UV light to activate the photoinitiators under moderate intensities of NIR excitation below 10 W cm −2 for free-radical polymerization ( Figure 9D). [146] This research found that the heterogenous distribution of photoluminescence intensity around UCNP would cause different morphologies of polymer growth from the surface of a single UCNP due to the different polymer growth kinetics. Moreover, it required a minimum concentration of UC-NPs to grow geometrically connected polymeric objects for 3D printing.…”
Section: Upcoversion Nanoparticles (Ucnps)mentioning
confidence: 87%
See 2 more Smart Citations
“…Recently, a high-resolution 3D photopolymerization was developed in which UCNPs, dispersed in a liquid mixture of photocurable composition, emitted UV light to activate the photoinitiators under moderate intensities of NIR excitation below 10 W cm −2 for free-radical polymerization ( Figure 9D). [146] This research found that the heterogenous distribution of photoluminescence intensity around UCNP would cause different morphologies of polymer growth from the surface of a single UCNP due to the different polymer growth kinetics. Moreover, it required a minimum concentration of UC-NPs to grow geometrically connected polymeric objects for 3D printing.…”
Section: Upcoversion Nanoparticles (Ucnps)mentioning
confidence: 87%
“…Adapted under the terms of the Creative Commons Attribution 4.0 International License. [146] Copyright 2018, Springer Nature.…”
Section: Upcoversion Nanoparticles (Ucnps)mentioning
confidence: 99%
See 1 more Smart Citation
“…This polymerization allows fabrication of 3D polymeric structures inside photocurable compositions, which was similar to two‐photon polymerization. This UCNP‐assisted photopolymerization could also be potentially utilized for control of formation of 3D shapes with a non‐contact manner inside tissues …”
Section: Applications Based On Ucnp‐assisted Photopolymerizationmentioning
confidence: 99%
“…and comparable photoactivation to standard Pi [112], gold nanoparticles are promising in biological applications as a replacement for standard PIs. Finally, enhanced and/or controlled photosensitivity can be realized with other nanoadditives such as ZrO 2 [161] or upconverting lanthanide-doped upconversion materials [162]. Thus, this approach can be considered to be extremely versatile and applicable to multiple materials.…”
Section: Inorganic Modificationsmentioning
confidence: 99%